Epithelial ovarian cancer in Greece: A retrospective study of 1,791 patients by the hellenic cooperative oncology group (HeCOG) - Pectasides, D.; Papaxoinis, G.; Fountzilas, G.; Aravantinos, G.; Bamias, A.; N. Pavlidis; Kalofonos, H.P.; Timotheadou, E.; Samantas, E.; Briasoulis, E.; Skarlos, D.V.; Economopoulos, T.; et al. (Anticancer Research, 2009)
Background: The aim of this retrospective study was to present the epidemiological, pathological and clinical characteristics and treatment results of Greek women with epithelial ovarian cancer (EOC). Patients and Methods: From February 1976 to December 2006, 1,791 patients had been diagnosed, treated and followed up in the participating centers of the Hellenic Cooperative Oncology Group (HeCOG). Cox-regression analysis was carried out in order to identify possible prognostic factors. Results: The median age at diagnosis was 60 years. Seventy-five percent had a performance status (PS) of 0-1, 58.5% had a serous carcinoma, 36% had poorly differentiated tumors and 57% had International Federation of Gynecology and Obstetrics (FIGO) stage III disease. Approximately half of the patients had been subjected to a total abdominal hysterectomy, bilateral oophorectomy and omentectomy, and 80% of them had undergone optimal debulking surgery. Among 1,462 patients with advanced disease, 96% had received platinum-based chemotherapy, while platinum plus paclitaxel had been administered to two-thirds of them. Among 609 patients with known data for response, 34% had achieved a complete objective response (CR) and 30% a partial response (PR), resulting in an overall response rate (RR) of 64%. Performance status, FIGO stage and residual disease (RD) after cytoreductive surgery were the strongest prognostic factors for time-to-tumor progression (TTP) and for overall survival (OS), while age was found to be significant only for OS. The median TTP was 107 months (95% confidence interval (CI), 92-121 months) for patients with stages I-II, 17 months (95% CI, 15-18 months) for those with stages III-IV, 96 months (95% CI, 58-133 months) for patients without RD and 17 months (95% CI, 15-18 months) for those with RD. Median OS had not been reached for the patients with stages I-II, while it was 40 months (95% CI, 37-43 months) for those with stages III-IV, 141 months (95% CI, 103-179 months) for patients without RD and 42 months (95% CI, 39-45 months) for those with RD. Conclusion: There were no significant differences in patient characteristics or types of treatments administered in Greek women with EOC in comparison with those reported in the English literature.
Keywords: Epithelial ovarian cancer; Prognostic factors; Registry; Retrospective